417 An Evaluation Of Digestibility and Caloric Value Of Different Botanical Parts Of Corn Residues Fed To Cattle. (7th December 2018) - Petzel, E; Smart, A; Hales, K; Foote, A; Acharya, S; Wright, C; Brake, D
Abstract: Grazing cattle often select diets with greater digestibility and presumably greater energy concentration in comparison to the average of the overall biomass available for grazing. Thus, estimates of diet energy based on measures of concentrations of chemical components in samples of mechanically harvested corn residues are unlikely to be strongly correlated to diets selected by grazing cattle. We used 6 ruminally cannulated cows in a replicated 3 x 3 Latin square experiment to determine energy balance, apparent nutrient digestibility and N retention using indirect respiration calorimetry in cattle fed diets of individual components of corn residues. Gross energy intake was greater (P < 0.01) when cows were fed leaf (18.0 Mcal/d) compared to husk and stalk (13.0 and 12.8 Mcal/d, respectively). Digestible energy (% of GE) was least (P < 0.01) and fecal energy was greatest (P < 0.01) when cows were fed stalk compared to husk or leaf. Metabolizable energy (% of DE) was greatest (P < 0.01) for leaf, intermediate for husk and least for stalk. Interestingly, energy lost as methane (% of DE) was nearly 68% greater when cattle were fed husk or stalk compared to leaf. Heat production (Mcal/d) during feeding or fasting was not different (P ≥ 0.81) when cows were fed leaf, husk or stalk. Subsequently, NEm (Mcal/kg DMI) was greatest (P < 0.01) for leaf (1.46) than husk (0.90) or stalk (0.68). Retained N was greatest (P < 0.01) for cows fed leaf compared to husk and stalk. Despite differences in measures of NEm and N retention, total-tract digestion of NDF and ADF were greatest (P < 0.01) for husks, least for stalks and intermediate for leaf. Overall, these data indicate that differences in total-tract digestion and ruminal methane production impact energy available to grazing cattle from different components of corn residue.